Aggregate price effects of institutional trading: a study of mutual fund flow and market returns - Edelen, Roger M; Warner, Jerold B (Journal of Financial Economics, 2001)
We study the relation between market returns and aggregate flow into U.S. equity funds, using daily flow data. The concurrent daily relation is positive. Our tests show that this concurrent relation reflects flow and institutional trading affecting returns. This daily relation is similar in magnitude to the price impact reported for an individual institution's trades in a stock. Aggregate flow also follows market returns with a one-day lag. The lagged response of flow suggests either a common response of both returns and flow to new information, or positive feedback trading.